2007
DOI: 10.1111/j.1525-1594.2007.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro and In Vivo Study of the Detection and Reversal of Venous Collapse During Extracorporeal Life Support

Abstract: The objective of this study was to investigate venous collapse (VC) related to venous drainage during the use of an extracorporeal life support circuit. A mock circulation was built containing a centrifugal pump and a collapsible vena cava model to simulate VC under controlled conditions. Animal experiments were performed for in vivo verification. Changing pump speed had a different impact on flow during a collapsed and a distended caval vein in both models. Flow measurement in combination with pump speed inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…4) was the result of substantial cannula obstruction and/ or caval vein occlusion with extreme luxation. In a previous study, we showed that such a decrease in the DFI is indicative of insufficient volume available for drainage [11]. The present study demonstrates that even small changes in DV can be detected by DFI measurement.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…4) was the result of substantial cannula obstruction and/ or caval vein occlusion with extreme luxation. In a previous study, we showed that such a decrease in the DFI is indicative of insufficient volume available for drainage [11]. The present study demonstrates that even small changes in DV can be detected by DFI measurement.…”
Section: Discussionmentioning
confidence: 42%
“…Although the effect of luxating the heart created reproducible changes in DFI, we did not obtain in our patients alternative evidence for the absolute changes in DV. In previous studies performed under well-controlled conditions we have demonstrated that the DFI responds straightforwardly to caval vein constriction and changes in transmural pressure at the drainage site [11]. The DFI may also be affected by a change in arterial line pressure.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The loops illustrate that resolving impaired drainage due to inappropriate pump speed (plateau in the curve) firstly requires a speed reduction, after which an increase of pump speed will restore the balance between venous return and venous drainage. 10 In a recent study, we demonstrated that small changes in DV, as reflected by the slope of the speed-flow curve (Figure 1 right) can be determined by measuring the dynamic filling index (DFI). 12 This index proved more sensitive to changes in DV than direct haemodynamic and pump-related parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we developed a technique to quantitatively assess venous volume that can be (potentially) drained by the centrifugal pump-based ELS circuit, and introduced the dynamic filling index (DFI, in ml/rotation) for the purpose of optimizing ELS flow [6-8]. DFI measurement uses periodical, transient reductions (-100 rpm) of pump speed, each lasting approximately 10 seconds, superimposed on the steady state pump speed.…”
Section: Introductionmentioning
confidence: 99%